2019
DOI: 10.5194/angeo-2019-11
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decrease of total electron content during the 9 March 2016 total solar eclipse observed at low latitude stations, Indonesia

Abstract: Abstract. The total solar eclipse on 9 March 2016 was a rare phenomenon that could be observed in 12 provinces in Indonesia. The decline in solar radiation to the earth during a total solar eclipse affects the amount of electron content (TEC) in the ionosphere. The ionospheric dynamics during the eclipse above Indonesia have been studied using data from 40 GPS stations distributed throughout the archipelago. It was observed that TEC decrease occurred over Indonesia during the occurrence of the total eclipse. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In particular, eclipse studies for the December 26, 2019 event have benefited from several early research work by Chandra et al (1997Chandra et al ( , 2007 [6,7], Sharma et al (2010) [4], Coster et al (2017) [8], for example, show decrease in electron density of ionosphere during the solar eclipses and coverage of groundbased monitoring GPS segments. GPS data were also used in many studies to analyze the TEC variation during the solar eclipse, e.g., Baran et al (2003) [9] accounted for the depression of TEC amounted to 2 -8 TECU during the solar eclipse of August 11, 1999. Srigutomo et al (2019 [10] has additionally shown that the rate of depletion of TEC is proportional to the magnitude of the eclipse, which is directly associated with the photoionization process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, eclipse studies for the December 26, 2019 event have benefited from several early research work by Chandra et al (1997Chandra et al ( , 2007 [6,7], Sharma et al (2010) [4], Coster et al (2017) [8], for example, show decrease in electron density of ionosphere during the solar eclipses and coverage of groundbased monitoring GPS segments. GPS data were also used in many studies to analyze the TEC variation during the solar eclipse, e.g., Baran et al (2003) [9] accounted for the depression of TEC amounted to 2 -8 TECU during the solar eclipse of August 11, 1999. Srigutomo et al (2019 [10] has additionally shown that the rate of depletion of TEC is proportional to the magnitude of the eclipse, which is directly associated with the photoionization process.…”
Section: Introductionmentioning
confidence: 99%
“…GPS data were also used in many studies to analyze the TEC variation during the solar eclipse, e.g., Baran et al (2003) [9] accounted for the depression of TEC amounted to 2 -8 TECU during the solar eclipse of August 11, 1999. Srigutomo et al (2019 [10] has additionally shown that the rate of depletion of TEC is proportional to the magnitude of the eclipse, which is directly associated with the photoionization process.…”
Section: Introductionmentioning
confidence: 99%
“…The Fountain effect is achieved by the decrease in the E×B plasma drift at low latitudes, and the strength of the Fountain effect will weaken when a solar eclipse occurs. As a result, the electron transport process will also decrease at low latitudes, which induces a decrease in TEC value in the low latitude region [8,11]. And the longitude depends on local time, being equal to 1-hour local time with 15 o longitude.…”
Section: Introductionmentioning
confidence: 99%